Comparation of abdominal aortic balloon occlusion versus uterine artery embolization in the treatment of cesarean scar pregnancy - Rui, Tan; Wei, He; Huaibo, Jing; Han, Mou; Cheung, Kenneth C. P.; Yang, Chai (Frontiers in Medicine, 2024)
Study Objective: This study is to uncover the advantages of abdominal aortic balloon occlusion in the uterine curettage treatment for patients with cesarean scar pregnancy (CSP).To retrospectively analyze the clinical data of eighty patients with CSP after treatment in our hospital from 01/10/2019 to 01/05/2021. The 80 patients were divided into 2 groups: 41 patients were treated with abdominal aortic balloon occlusion and the control group (n = 39) underwent Uterine artery embolization(UAE). The amount of bleeding during the operation, the operation time of the uterine curettage, the X-ray fluoroscopy time under DSA, the surface dose in radiation, the length of hospital stay (LOS), and the postoperative complications were compared between these 2 groups(type Ⅱ and type Ⅲ).Results: All the operations successfully retained the uterus. No balloon-related complications occurred in the experimental group. And in the control group, there were 14 cases of fever and 19 cases of pain after UAE. The fluoroscopy time of experimental group and control group were: (type Ⅱ: (20.3±7.1)s vs (593.7±284.5)s, P<0.01), (type Ⅲ: (21.2±7.2)s vs (509.8±164.2)s, P<0.01), the surface dose in radiation: (type Ⅱ: (1.9±0.7)mGy vs (248.3±85.9)mGy, P<0.01), (type Ⅲ:(2.1±0.8)mGy vs(252.0±74.9)mGy, P<0.01), the amount of bleeding during the operation: (type Ⅱ:30.0(20.0,50.0)ml vs 20.0(10.0,50.0)ml, P=0.113), (type Ⅲ:50.0(17.5,162.5)ml vs 50.0(22.5,72.5)ml, P=0.623), the operation time of the uterine curettage:(type Ⅱ: (54.8±19.4)min vs(43.9±21.9)min, P=0.071), (type Ⅲ: (65.2±50.4)min vs(52.8±20.1)min, P=0.426), LOS: (type Ⅱ:(5.4±1.7)d vs(5.4±1.2)d, P=0.816), (type Ⅲ:(5.8±2.4)d vs (7.0±1.7)d, P=0.161). The follow-up was more than three months. No adverse reaction in the experimental group and 6 patients in the control group presented menstrual volume decrease. Conclusions: No balloon-related complications occurred in the abdominal aortic balloon occlusion and lower radiation exposure for both the operator and patient,. And both abdominal aortic balloon occlusion and UAE can effectively reduce the bleeding during uterine curettage in patients with type Ⅱ and Ⅲ CSP.